THE MECHANISM OF ADMINISTRATIVE AND LEGAL PROVISION OF THE ACTIVITIES OF NON-STATE PENSION FUNDS IN UKRAINE (Law and Safety, 2018)
On the basis of the analysis of scientific points of view of scholars and the current legislation of Ukraine, the authors have studied the definition of “the mechanism of administrative and legal provision of the activities of non-state pension funds”.It has been established that the mechanism of administrative and legal provision of the activities of non-state pension funds covers an integral complex of administrative and legal means aimed at regulating relations in the field of non-state pension provision (hereinafter – NSPP) and protecting and satisfying the interests of individuals and legal entities-depositors by the subjects of public administration – the state agencies of control and supervision.The structure of the studied mechanism according to the authors includes the following elements (means): the norms of administrative law, objectively expressed in the laws and other normative acts; administrative and legal relations; acts of application of the norms of administrative law; acts of interpretation of the norms of administrative law; legal awareness; legal culture; legality.It has been noted that the effectiveness of the implementation of administrative and legal influence by the control and supervision agencies in the system of NSPP requires the state to provide a flexible regulatory base, accessible information space, relevant directions of the use of pension funds; the establishment of investment rules with the definition of diversification criteria, rules for calculating the net value of pension assets, rules for the storage of pension assets and supervisory functions of the custodian bank, rules for conducting an external audit of pension funds.The directions of the activities of administrative apparatus in the field of NSPP have been analyzed. It has been determined that pension income of non-state pension funds directly depends on the effectiveness of the mechanism of financial resources management, which is a system set of methods, levers and instruments of influence on the processes of formation, investment and use of the financial resources of the fund in order to preserve and increase the pension savings of the participants.